Aspects of Selection in Barley under Saline Irrigation - Yadav, R S (Annals of Arid Zone, 2016)
Genetic correlation of tolerance and mean productivity with one another and with yield in saline and non-saline environments were calculated in terms of ratio of genetic variances and the genetic correlations between yield in stress and non-stress environments. Selection for mean productivity showed high positive genetic correlation to yield in both the environments. For increased yield in saline environment,one should go for selection for mean productivity. Selection for tolerance will decrease both mean productivity and mean yield in both the environments.